Auch eine Gewerkschaft? Der Deutschnationale Handlungsgehilfenverband und die Angestellten - Martin Otto (Rechtsgeschichte - Legal History, 2022)
During the Weimar Republic, German white-collar workers (Angestellte) preferred non-socialist trade unions. Socialist ›free unions‹ (freie Gewerkschaften) only played a minor role among middleclass employees. The biggest union by far was the »German National Union of Commercial Employees« (Deutschnationaler Handlungsgehilfenverband, DHV) with 400.000 exclusively male and mostly protestant members. Founded in Hamburg in 1893, with roots in Adolf Stoecker’s nationalist Christian social movement, it defined itself explicitly as a Christian union with anti-socialist and also antisemitic tendencies.The number of commercial employees rose during the German Empire, and most clerks obviously lacked any chance of becoming independent. The new category of employees, who saw themselves as strongly distinct from manual workers, was neglected by the political Left. The right-wing DHV offered its members a vast number of social activities as well as housing and insurance, and even owned a number of publishing companies. However, it acted like any union in terms of providing advice to its members and negotiating wage agreements, nor did it hesitate to initiate strike action. Already before the First World War, the DHV moved towards a more pragmatic position. In labour law, it favoured special corporatism with proposals partly similar to those of socialist and liberal unions. In 1928, the DHV leadership broke with Hugenberg’s DNVP and began supporting the democratic conservatives. Although many of its members turned into ardent National Socialists, other members and officials became part of the German resistance. After 1945, the difficult heritage of the DHV led to the creation of the Deutsche Angestelltengewerkschaft (›German EmployeesUnion‹), which took on the role of an independent union for white-collar workers outside the ›unitarian‹ DGB.